Booster dose of COVID-19 vaccination: Perception among elderly - Heltty, Heltty; Palingrungi, Basso; Apriyanti, Apriyanti (The Journal of Palembang Nursing Studies, 2023)
Background: COVID-19 is still a health problem that needs to be addressed. COVID-19 vaccination had been promoted but its coverage was still low, including coverage for the elderly. Objective: This study aimed to investigate the elderly’s perception of participation in COVID-19 vaccination of booster dose. Methods: This research was a qualitative descriptive study. Collected informants using purposive sampling method. Semi-structured in-depth interviews with nine informants who were domiciled in Kendari, Indonesia. Data analysis using thematic analysis approach.  Results: There were three things related to the perception of the elderly in participating in booster dose COVID-19 vaccinations that have been identified. These three things were the elderly’s perception of the COVID-19 vaccination, doubts about the COVID-19 vaccine, and family support. Conclusions: The elderly’s perception of COVID-19 vaccination can help determine the next intervention that can help increase vaccination coverage among elderly. The need to increase understanding of COVID-19 vaccination to the elderly through clear, comprehensive, easy-to-understand, and easily accessible information.